The practice of social research - Babbie, Earl R. (Belmont, Calif : Wadsworth Cengage, 2007)
This is a comprehensive, straightforward introduction to the field of research as practiced by social scientists. This best-selling book emphasizes the research process by demonstrating how to design research studies, introducing the various observation modes in use today, and answering questions about research methods--such as how to conduct online surveys, and analyze both qualitative and quantitative data. The practice of social research provides all the tools researchers and consumers need to apply social research.
Includes bibliographic references and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology